An Informetric Perspective of Intellectual Property Research in Africa using the SCOPUS Database - Ngwenya, Sibongile; Onyancha , Omwoyo Bosire (Mousaion: South African Journal of Information Studies, 2024)
Intellectual property (IP) issues are addressed globally through multilateral instruments, such as the trade-related aspects of intellectual property rights (TRIPs). Such global settings may be inadequate to consider African regional issues. However, the discourse regarding IP in the African region seems to be limited. This study was conducted to examine documents on IP in Africa with the aim of determining the availability of publications and establishing the obstacles that hinder scholarly publishing on IP in Africa. This was a quantitative study conducted on SCOPUS on 14 August 2023, using the search term “intellectual property in Africa,” which retrieved a total of 2 316 documents (2000–2022). The results showed that, out of the 50 countries with documents on IP in Africa, only 11 were African countries, while six of the 10 institutes were universities in Africa. The publications were in 12 document types, and there were five dominant subject areas. Only three out of the 10 prominent authors were affiliated with institutions in Africa, and none of the top five journals belonged to an African country. Only one funding sponsor and one language were African. The researchers concluded that publications on IP in Africa were available in a variety of types, cutting across disciplines. However, they were very few and limited to certain years, countries and institutions due to issues of authorship, source, funding sponsor, and language of publication. There is a need to raise awareness of the need for scholarly discourse regarding IP in the African context.